Cognitive waveform design for radar-communication transceiver networks - Yu YAO; Yanjie LI; Lenan WU; Pu MIAO; Xiaoyu TANG (物联网学报)
The system architecture for cognitive radar-communication (CRC) transceiver was proposed.A cognitive waveforms design approach, which is suitable for simultaneously performing both data communication and target detection was presented.This approach aims at estimating target scattering coefficient (TSC) from the radar scene and facilitating high-data-rate communications.In order to minimize the mean square error (MSE) of the TSC, a convex cost function was established.The peak to average power ratio (PAPR)-constrained optimal solution was achieved by applying the Kalman filtering-based strategy to design the set of ultra-wideband (UWB) transmission pulses and embed into them the information data with the M-ary position phase shift keying modulation technique.In addition to theoretical considerations, the simulation results show an improvement in TSC estimation and target detection probability as the number of iterations increases, while still transmitting data rates in the range of several Mbit/s with low bit error rates between CRC transceivers.